Primary Bone Tumor of the Spine—An Evolving Field: What a General Spine Surgeon Should Know. Issue 1 (May 2019) - Charest-Morin, Raphaële; Fisher, Charles G.; Sahgal, Arjun; Boriani, Stefano; Gokaslan, Ziya L.; Lazary, Aron; Reynolds, Jeremy; Bettegowda, Chetan; Rhines, Laurence D.; Dea, Nicolas
Study Design: A narrative review of the literature. Objective: This article reviews the general principles of treatment and investigation for primary bone tumors of the spine. Furthermore, it explores the emerging alternatives. Methods: A review was performed using Medline, Embase, and Cochrane databases. Results: Primary bone tumors of the spine are rare entities that general spine surgeons may encounter only a few times in their career. The treatment algorithm of these complex tumors is filled with nuances and is evolving constantly. For these reasons, patients should be referred to experienced tertiary or quaternary centers who can offer a comprehensive multidisciplinary approach. For most malignant spinal bone tumors, surgery remains the cornerstone of treatment. Respecting oncologic principles has been associated with improved survival and decreased local recurrence in multiple settings. However, even in experienced centers, these surgeries carry a significant risk of adverse events and possible long-term neurologic impairment. The associated morbidity of these procedures and the challenges of local recurrence have encouraged professionals caring for these patients to explore alternatives or adjuncts to surgical treatment. Conclusions: Over the past few years, several advances have occurred in medical oncology, radiation oncology and interventional radiology, changing the treatment paradigm for some tumors. Other advances still need to be refined before being applied in a clinical setting.